Transjugular intrahepatic porto-systemic shunt is a risk factor for liver dysplasia but not hepatocellular carcinoma: A retrospective study of explanted livers. Issue 1 (January 2015) - Borentain, Patrick; Garcia, Stephane; Gregoire, Emilie; Vidal, Vincent; Ananian, Pascal; Ressiot, Emmanuelle; Hardwigsen, Jean; Bartoli, Jean-Michel; Moulin, Guy; Botta-Fridlund, Danielle; Le Treut, Yves Patrice; Gerolami, Rene
Abstract: Background: Conflicting data exist regarding the risk for hepatocellular carcinoma after transjugular intrahepatic porto-systemic shunt (TIPS) insertion in cirrhotic patients. Methods: We retrospectively analysed histopathological data from 214 patients who were transplanted in our Institution including 68 patients who underwent TIPS placement before transplantation. Pathological lesions from explanted livers, including incidental hepatocellular carcinoma, small cell dysplasia and large cell dysplasia were recorded. Results: Pathological lesions were found in 36.4% of explanted livers. TIPS insertion was an independent risk factor for pathological lesion (HR = 2.11, p  < 0.05), concurrently with age (HR = 1.10 per year, p  < 0.001) and viral aetiology of cirrhosis (HR = 3.05, p  < 0.001). When considering the different type of lesions, TIPS insertion was not associated with an increased risk for hepatocellular carcinoma but was an independent risk factor for liver dysplasia (HR = 2.15, p  = 0.042). Conclusion: Although a direct relationship between TIPS insertion and hepatocellular carcinoma risk was not demonstrated in this study, the increased frequency of liver dysplasia observed in TIPS-bearing explanted livers deserves further prospective investigations with adequate follow-up.